England in a Miniature in Mike Leigh’s "The Short and Curlies" - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Mike Leigh’s films are known for having kept the same tone and having played out the same melody for years. It is noteworthy that all the themes which Mike Leigh developed in his subsequent films, appeared in The Short and Curlies. Short scenes from the life of the English in The Short and Curlies can be seen in each scene of the film. From details such as a street with a perfectly straight terrace of houses with small gardens to social questions that are constant in the British culture. This ordinary, everyday observation gave rise to the plot of The Short and Curlies, revolving around a love affair of Joy (Sylvestra Le Touzel), a young woman working at a chemist’s and Clive (David Thewlis), a man who communicates with her only by means of his humourless jokes. Another story in the film is a complicated relationship of an eccentric hairdresser Betty (Alison Steadman), who is more interested in the life of the pharmacist than in the life of her own daughter Charlene (Wendy Nottingham). As Ewa Mazierska says: “Mike Leigh was once called the painter of miniatures – his films and TV productions for which he is equally praised and admired, concentrate on life of «small people with small gardens»”. Mike Leigh knows that his strengths are well written dialogues and this extraordinary skill to become a fictional character possessed by the actors he chooses.